IMIDACLOPRID TOXICITY AND ITS ATTENUATION BY AQUEOUS EXTRACT OF MORINGA OLEIFERA LEAF IN ZEBRA FISH, DANIO RERIO - YADAV, VINEETA; AHMAD, SHADAB; ZAHRA, KANEEZ (International Journal of Current Pharmaceutical Research, 2020)
Objective: Imidacloprid (IMC) is a systemic chloro-nicotinyl insecticide that is applied in crop fields to control a wide variety of harmful insects and pests. The objective of the present study was to evaluate the mitigating effects of Moringa leaf extract (MLE) against Imidacloprid (IMC) induced mortality after acute toxicity bioassay in zebrafish, Danio rerio. Methods: The fishes were exposed to various concentrations of IMC to estimate the LC50 values at different exposure periods using the probit analysis. To assess the attenuating effect on mortality fishes were exposed to different concentrations of MLE along with 24 and 96 h LC50 of IMC. Mortality rate of fishes was recorded during all experimental periods. Results: The LC50 values were found to be 0.423, 0.352, 0.297 and 0.270 ml/l after 24, 48, 72 and 96 h respectively. The upper confidence limits were 0.491, 0.408, 0.334 and 0.302 ml/l and lower confidence limits were 0.355, 0.296, 0.260 and 0.238 ml/l for 24, 48, 72 and 96 h respectively. The fishes remain alive at 12 ml/l and 10 ml/l of MLE against 24 and 96 h LC50 respectively. Some behavioral responses such as violent, sluggish and erratic movement, respiratory distress, mucous secretion all over the body, discoloration were also observed in IMC treated fishes in comparison to MLE treated fishes. Conclusion: These findings demonstrated that MLE has mitigating effects against the toxic influence of IMC on mortality in zebra fishes which is attributed to its antioxidant effects.